2018
DOI: 10.1111/vop.12561
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure reference intervals in eyes of clinically normal miniature donkeys (Equus africanusasinus)

Abstract: Reference intervals for IOP's were established for this species. Intraocular pressure readings obtained by the rebound tonometer were significantly higher than with applanation. Sedation and AP block did not affect IOP estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Intraocular pressure is known to be lower in infants than in adults and to decrease again with age in humans, dogs, cats, and lions 2,25 . A recent study suggested that IOP may decrease with age also in miniature donkeys 22 . Newborn foals have been reported to have IOP readings similar to adult horses 27,28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraocular pressure is known to be lower in infants than in adults and to decrease again with age in humans, dogs, cats, and lions 2,25 . A recent study suggested that IOP may decrease with age also in miniature donkeys 22 . Newborn foals have been reported to have IOP readings similar to adult horses 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Proper evaluation and care of an ophthalmic patient necessitate the ability to interpret IOP readings correctly. Previous studies have demonstrated variation in tonometrically evaluated normal IOP range values in horses and in other animals, and thus, it is mandatory for the clinician to consider the information available for the device used 6‐8,13,21‐24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the intraocular pressure was measured only in those animals displaying signs indicative of uveitis, glaucoma or corneal oedema. Since this study was performed, Hibbs et al16 have recently demonstrated that the presence or absence of sedation and/or an auriculo‐palpebral nerve had no effect on IOP estimates in miniature donkeys. Similarly, a study by Ghaffari et al17 was able to reliably measure intraocular pressure without the use of sedation or nerve blocks.…”
Section: Discussionmentioning
confidence: 88%
“…Ghaffari et al17 reported a mean IOP of 17.8 ± 3.7 mm Hg, with a range of 13.5‐24.5 mm Hg, using applanation tonometry in adult donkeys. In another study, Hibbs et al16 reported a mean IOP of 25.75 ± 5.70 mm Hg, with a range of 14.34‐37.15 mm Hg using rebound tonometry in miniature donkeys. No studies to date have reported the reference interval for intraocular pressure measurement in normal adult donkeys using rebound tonometry.…”
Section: Discussionmentioning
confidence: 95%